Rocking the boat to change the debate: Identifying and testing conventional wisdom - Reardon, Thomas (Wiley, 2025)
This paper presents a method for and experiences with pioneering new research directions that challenge “conventional wisdom” and change policy and research debates. The method consists of four steps: (1) identify the conventional wisdom (CW); (2) ignore the CW and go to the field without pre-conceived notions, and look long and hard at reality—with interviews and surveys broad enough to allow oneself to make discoveries that contradict the CW; (3) then identify the contradictions between the CW and the field discoveries and pinpoint the implications for policy and research debates; (4) develop and mainstream a new research theme along a research “product cycle.” The paper summarizes my and collaborators’ application of the method with illustrations from four waves of market economics field research in Africa, Asia, and Latin America since the 1980s: (a) rural nonfarm employment; (b) processed food consumption; (c) the “hidden middle” (rapid diffusion of small and medium enterprises in the midstream of value chains); and (d) the “supermarket revolution”. The paper ends with a discussion of the benefits of this approach to policy and research debates and the researcher's own career, as well as considerations of risks, timing, and approach for application of the method.